SMAD phosphorylation and the TGF-beta pathway - Massagué, Joan (Henry Stewart Talks, 2010)
The TGFb family as a paradigm of multifunctional cytokines, TGFb controlling embryo development and tissue homeostasis, TGFb receptor serine/threonine kinases, SMADs as central TGFb signal transducers and transcriptional mediators, Logic and organization of TGFb signaling processes, TGFb pathway regulation and integration in the cell, TGFb pathway disruption in heritable disorders and cancer